Youth and telecentres in community building in rural Peninsular Malaysia - Abu Samah, Bahaman; Badsar, Mohammad; Abu Hassan, Musa; Osman, Nizam; Mohamed Shaffril, Hayrol Azril (Universiti Putra Malaysia Press, 2013)
This paper aims to investigate the factors that affect telecentres in community building in the perspective of youth in rural Peninsular Malaysia. The perspective of youth on developing a model for telecentres in community building is important as: 1) youth are at the forefront of adoption of new technology, 2) youth as a group are the highest number of users of telecentres, and 3) youth are tasked with the responsibility of building up the community in the near future. This paper employed a cross-sectional survey method to achieve the study objectives. Data collected were from 313 youth randomly selected from the users of Medan Info Desa (MID) and Program Internet Desa (PID) telecentres in rural Peninsular Malaysia. The results of the Structural Equation Modelling (SEM) analyses show that the proposed model explains 47% variability on the influence that telecentres have in community building from the point of view of youth. Furthermore, all independent variables including information, telecentre and community characteristics were significantly related to the influence telecentres have in community building; characteristics related to information form the more powerful predictor. Possible measures that the government and donor agencies can implement as implied from these findings are also discussed.